Supporting primary health care in Mongolia experiences, lessons learned, and future directions. - Jigjidsuren, Altantuya (East Asia working papers., 2020)
Since the early 1990s, ADB has broadly supported health sector reforms in Mongolia. PHC reform in the country aimed at facilitating a shift from hospital based curative services toward preventive approaches. It included introducing new management models based on public private partnerships, increasing the range of services, applying more effective financing methods, building human resources, and creating better infrastructure. The paper outlines remaining challenges and future directions for ADB support to PHC reform in the country.